The Correlation Between Maternal Anemia, Newborn Baby Weight and Long Intranatal Stage II at Dr. H. Moch. Ansari Saleh Hospital Banjarmasin. - Rizqy Amelia; R Topan Aditya Rahman; Hafidzu Dyta Covaria (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2018)
Background: Long intranatal is one of the causes of maternal mortality. The long Intranatal is classified into 3 phases, long latent phase, long active phase, and Long Intranatal Stage II. Long intranatal stage II causes the maternal mortality of 8% in the world, and 9% in Indonesia.Objective: To identify and Analyze Correlation between maternal anemia, Newborn baby Weight and long intranatal stage II at Dr. H. Moch. Ansari Saleh Hospital Banjarmasin.Methods: The research used an analytical survey with case control approach. Sampling techniques in this research was total sampling. Data was collected by by using checklist and data processing by using chi square test.Results: Chi square test showed that there was a significant relationship between maternal anemia p = 0.000 with OR 18,627, so maternal anemia has more risk than no anemia to have experience long intranatal stage II. Also infant birth weight born p = 0,004Â  with OR 3,583, so the normal infant birth weight (2500-4000gr) has more risk than 4000 gr to long intranatal stage II.Conclusion: there was a significant correlation between maternal anemia, newborn baby weight and long intranatal stage II.Keywords: Newborn Baby Weight, Maternal,Â  Anemia, Long Intranatal Stage II o-ansi-language